(untitled) (Journal of University of Babylon for Engineering Sciences, 2024)
In this research, poly acrylate-acrylamide (P-AM) was incorporated into an iron (Fe3O4@SiO2) ‎nanocomposite to develop a Fe3O4@SiO2/P-AM adsorption material for Cu (II) ion adsorption. First, Fe3O4 was ‎synthesised, then coated with Silica, and ultimately, Fe3O4@SiO2/P-AM was produced using the co-precipitation ‎method. Meanwhile, The aqueous phase dispensability of the Poly acrylate-acrylamide (P-AM) material increases ‎inclusion adsorption efficacy and the adsorption process. The polymer’s structural and morphological characteristics ‎were cautiously studied utilising advanced techniques such as XRD, FE-SEM, EDX, TEM, AFM, FTIR, and BET ‎surface area characterization. Pleasantly, the Fe3O4@SiO2/P-AM nanocomposite displayed substantially higher ‎adsorption effectiveness than its component elements, resulting in a remarkable removal rate of about 89.3% during ‎‎360 minutes. The adsorption process was fully examined, with four independent factors taken into account: periods ‎of time ranging from 5 to 360 minutes, solution’s pH is ranging from 3 to 12, adsorbent dosage ranging from 1 to 3 ‎g/L, and Cu (II) concentration ranging from 25 to 125 mg/L. The best parameters for removing copper metal by ‎adsorption utilising Fe3O4@SiO2/P-AM as adsorbent material were pH 7, 3 g/L dosage of adsorbent, contact time ‎‎360 min, and starting Cu (II) ion concentration of 25 mg/L, according to the experimental results. Furthermore, the ‎Langmuir Isotherm was used to analyse and characterise the adsorption process, with regression (R2) of 0.99 ‎indicating the best match to the equilibrium data. According to this definition, the process is mono‏-‏layer adsorption ‎on a homogenous adsorbent surface with no contact between the adsorbed molecules. In comparison to other models, ‎the Kinetic analysis reveals that the experimental data matches pseudo-second-order model (R2 =0.99). Furthermore, ‎because it is magnetic and stable, it is extremely likely to be employed in practise‏.‏